2014
DOI: 10.1016/j.rmed.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Initial characteristics and outcome of hospitalized patients with amiodarone pulmonary toxicity

Abstract: Severity of APT is linked to the extent and speed of onset of pulmonary damage. After the initial episode, the patients who survived improved slowly but with persistent sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 38 publications
(16 reference statements)
0
24
0
6
Order By: Relevance
“…A resolution of findings can occur over two to eight weeks. High-resolution CT can reveal diffuse bilateral ground-glass opacification, alveolar consolidation, intra-alveolar reticulations, and pleural effusions [11]. In this case, patient history, exam, and workup, including ECG, troponin, and echocardiogram, make cardiac pathology less likely.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A resolution of findings can occur over two to eight weeks. High-resolution CT can reveal diffuse bilateral ground-glass opacification, alveolar consolidation, intra-alveolar reticulations, and pleural effusions [11]. In this case, patient history, exam, and workup, including ECG, troponin, and echocardiogram, make cardiac pathology less likely.…”
Section: Discussionmentioning
confidence: 95%
“…Treatment with systemic corticosteroids was found in one study to induce relapse when treatment lasted for less than three months but not longer than six months, probably attributable to the 40-70 day half-life elimination of amiodarone and storage in the lung parenchyma. Positive effects were noted on alveolar opacifications [11]. An initial dose of 0.75-1 mg/kg of prednisolone should be maintained until there is a definite clinical and radiographic response, as recurrence can be more severe than the initial episode.…”
Section: Discussionmentioning
confidence: 98%
“…. Outros fatores de risco incluem gênero masculino, doença pulmonar préexistente, idade avançada, exposição a altas concentrações de oxigênio 1,2,5,6,8 . Pneumonite aguda associada ao uso de amiodarona por curto período de tempo é muito mais rara.…”
Section: Discussionunclassified
“…3,4 Incidence/Risk Factor APT is a serious adverse event that occurs in approximately 2 to 5% of treated patients 5 and mortality at day 90 was reported to be 37%. 6 APT can develop as early as from the first few days of treatment to several years later and even after discontinuation of the therapy. 7 Viswam et al reported an incidence of APT on a 58-year-old male patient postcoronary artery bypass grafting after a day's loading dose of amiodarone.…”
Section: Discussionmentioning
confidence: 99%